Sarcoid-Like Reaction in the Kidney Following Rituximab for Mantle Lymphoma in a 60-Year-Old Man - Sanda Mrabet; Rihem Dahmene; Asma Fradi; Achraf Jaziri; Raja Boukadida; Awatef Azzebi; Wissal Sahtout; Narjess Ben Aicha; Dorsaf Zellama; Abdellatif Achour; Nihed Abdessayed; Moncef Mokni (American Journal of Men's Health, 2023)
The sarcoid-like reaction is a rare autoinflammatory disease that can affect lymph nodes or organs but does not meet the diagnostic criteria for systemic sarcoidosis. Several drug classes have been associated with the development of a systemic sarcoid-like reaction, which defines drug-induced sarcoidosis-like reactions and can affect a single organ. Anti-CD20 antibodies (rituximab) have rarely been reported as responsible for this reaction and this adverse effect has mainly been described during the treatment of Hodgkin’s lymphoma. We report a unique case of a sarcoid-like reaction complicating rituximab following the treatment of a mantle cell lymphoma and interesting only the kidney. The 60-year-old patient presented with severe acute renal failure 6 months after the end of his r-CHOP protocol and the urgent renal biopsy revealed acute interstitial nephritis rich in granulomas without caseous necrosis. After ruling out other causes of granulomatous nephritis, a sarcoid-like reaction was retained since infiltration was limited to the kidney. The temporal relationship between rituximab administration and the sarcoid-like reaction onset in our patient supported the diagnosis of a rituximab-induced sarcoidosis-like reaction. Oral corticosteroid treatment led to rapid and lasting improvement in renal function. Clinicians should be warned of this adverse effect and regular and prolonged monitoring of renal function should be recommended during the follow-up of patients after the end of treatment with rituximab.